Transmembrane peptides as unique tools to demonstrate the in vivo action of a cross-class GPCR heterocomplex - Lee, Leo T. O. (Federation of American Societies for Experimental Biology, 2014)
Angiotensin (ANGII) and secretin (SCT) share overlapping, interdependent osmoregulatory functions in brain, where SCT peptide/receptor function is required for ANGII action, yet the molecular basis is unknown. Since receptors for these peptides (AT1aR, SCTR) are coexpressed in osmoregulatory centers, a possible mechanism is formation of a cross-class receptor heterocomplex. Here, we demonstrate such a complex and its functional importance to modulate signaling. Association of AT1aR with SCTR reduced ability of SCT to stimulate cyclic adenosine monophosphate (cAMP), with signaling augmented in presence of ANGII or constitutively active AT1aR. Several transmembrane (TM) peptides of these receptors were able to affect their conformation within complexes, reducing receptor BRET signals. AT1aR TM1 affected only formation and activity of the heterocomplex, without effect on homomers of either receptor, and reduced SCT-stimulated cAMP responses in cells expressing both receptors. This peptide was active in vivo by injection into mouse lateral ventricle, thereby suppressing water-drinking behavior after hyperosmotic shock, similar to SCTR knockouts. This supports the interpretation that active conformation of AT1aR is a key modulator of cAMP responses induced by SCT stimulation of SCTR. The SCTR/AT1aR complex is physiologically important, providing differential signaling to SCT in settings of hyperosmolality or food intake, modulated by differences in levels of ANGII.—Lee, L. T. O., Ng, S. Y. L., Chu, J. Y. S., Sekar, R., Harikumar, K. G., Miller, L. J., Chow, B. K. C. Transmembrane peptides as unique tools to demonstrate the in vivo action of a cross-class GPCR heterocomplex.